Learning strategy in the fifth-year primary school textbook - Taybi, Issa (El Omda in Linguistics and Discourse Analysis, 2023)
The educational process aims to develop learning capacities and improve the conditions of success and acquisition, by following the evolution of modern educational systems, which are based on "scientific psychology», this latter has proved its credibility, according to an experimental database that takes into account the natural growth of the child and his willingness to acquire. We note this in the primary reading book of the fifth grade. There is a specific strategy in "learning" which is based on taking into account the competence of the pupil and his will at this level of education.